Imatinib for right heart failure in COPD. (1st December 2018) - Douschan, Philipp; Kovacs, Gabor; Foris, Vasile; Kuehnelt‐Leddihn, Maria; Olschewski, Horst
Abstract : Severe pulmonary hypertension (PH) is rare in chronic obstructive pulmonary disease (COPD). Pulmonary arterial hypertension drugs are vasodilators and may cause severe side effects in these patients. Hence, they are not recommended except in right heart failure on an individual basis. Imatinib, a tyrosine‐kinase‐inhibitor, has no direct vasodilator effects but significantly improved hemodynamics and exercise capacity in PAH but its use was associated with an increased risk for subdural hematomas in anticoagulated patients. We report on a COPD patient with right heart failure who did not recover with a phosphodiesterase‐5‐inhibitor or a soluble‐guanylate‐cyclasestimulator alone but with imatinib as add‐on therapy. After one year of treatment, pulmonary vascular resistance (10.8 WU to 2.9 WU), NT‐proBNP (4144 pg/mL to 363 pg/mL), and symptoms (WHO FC IV to III, 6MWD bedridden to 303 m) improved without major side effects. Imatinib may be a therapy option in patients with severe PH due to lung disease and right heart failure where other drugs have failed.